Divergent Responses of Summer Precipitation in China to 1.5°C Global Warming in Transient and Stabilized Scenarios. Issue 9 (15th September 2021) - Jiang, Zhihong; Hou, Qiyao; Li, Tim; Liang, Yongxiao; Li, Laurent
Abstract: Responses of summer precipitation in China to global 1.5°C warming with transient and stabilized pathways are investigated through the analysis of the Common Earth System Model climate simulations. Precipitation increases more significantly in southeast China in the stabilized scenario compared with the transient one. The difference is primarily attributable to dynamic factors related to circulation changes and driven by differences of land‐ocean thermal contrast between the two scenarios. The stabilized warming favors conditions of larger ocean warming and smaller land warming, leads to enhanced meridional temperature gradient and ultimately speeds up the jet stream over East Asia. Ageostrophic wind at the entrance of the accelerated jet strengthens ascending motion and precipitation along the coast of Asia from southeast China to India. The enhanced heating over India further induces a Kelvin‐wave response with an anomalous anticyclone that contributes to the enhanced westward shifted of the western North Pacific Subtropical High. Southerly winds at the west flank of the anticyclone transport moisture northward from tropical oceans, and strengthen precipitation in southeast China. Plain Language Summary: This study deals with the issue of regional precipitation response to 1.5°C global warming in accordance to the Paris Agreement on Climate Change for two different pathways, either transient or stabilized. Compared with the transient warming scenario, summer precipitation increases more significantly in southeast China in the stabilized one. This feature of distinctive precipitation responses, with strong implications for policy making in terms of regional climate mitigation and adaptation, is furthermore explored through a moisture budget analysis. Dynamic effect in relation to changes of atmospheric circulation is found to be the major contributor to the difference. The cause of the significant difference in precipitation in South China is attributed to changes of land‐ocean thermal contrast, leading to a series of atmospheric circulation adjustments. Results presented here satisfactorily addressed, for the first time, the long‐standing issue on global warming, namely, how the atmosphere responds distinctively under the transient and stabilized anthropogenic forcing pathways which show however an identical global warming level. Key Points: The summer precipitation increases more significantly in southeast China in the stabilized warming scenario compared with the transient one The dynamic effect in relation to changes of atmospheric circulation constitutes the major factor of distinctive precipitation responses The differential meridional thermal gradient related to a contrasted land‐ocean warming leads to dynamic changes